Teh herbal terstandar simplisia bunga gemitir (Tagetes erecta Linn.) sebagai kandidat antioksidan baru - Kadar Riansyah; Aliefman Hakim; Agriana Rosmalina Hidayati (Sasambo Journal of Pharmacy, 2023)
Empirically, gemitir flower (Tagetes erecta Linn.) has been used for generations as an alternative to treat whooping cough and eye pain medication. Gemitir flower is potential as an antioxidant because it contains secondary metabolites of phenolic groups, flavonoids, and alkaloids that have been shown to have antioxidant activity. As a pharmaceutical products, medicinal plants must be guaranteed quality and safety. This study aims to determine the suitability of the simplicia quality of gemitir flowers by standardization based on Indonesian Herbal Pharmacopoeia and Indonesian Materia Medica, and also to determine the antioxidant potential of standardized herbal teas of gemitir flowers. This first step of this research were standardization of gemitir flower simplicia based on specific and non-specific parameters, followed by making standardized herbal tea of gemitir flower. Antioxidant activity test was carried out on tea preparations using the DPPH method. The results showed that the simplicia of gemitir flower met all the standard parameters of specific and non-specific standardization with an ash content value of 3,47%, acid insoluble ash content of 0,11%, water soluble extract content of 24,86%, ethanol soluble extract content of 21,67%, drying shrinkage content of 9,33%, moisture content of 9,23% and foreign organic matter of 0,3%. Standardized herbal tea simplicia gemitir flower was able to inhibit 50% of DPPH free radicals at a volume of 33,87 µL. Based on the results, it can be concluded that the empirical use of gemitir flower tea potential as a natural antioxidant.